Patent Production in the State of Ceará: a comparative study between the public institutions of higher education, scientific and technology - Araujo, Geovane Gomes de (2018)
The objective of this study was to produce researches in the pedagogical institutions of research, science and technology from 2009 to 2017. The following institutions were analyzed: State University of Ceará (UECE), Federal University of Ceará (UFC), Regional University (UCA) and the Federal Institute of Education, Science and Technology of the State of Ceará (IFCE), the University of Cariri (URCA), the Federal University of Cariri (UFCA), the International Integration University of Afro-Brazilian Lusophony (UNILAB). This research was carried out through the research of bibliographic data and a pathological study, considering that the patents are important for the information on industrial development. The lags of the applications were checked, the number of patent applications filed, the series found revealed a large quantity, no period investigated. The year, the year has the development of the public activities have been an advance, in the issue of evolucion no aspect.